Shengyu decoction ameliorates knee osteoarthritis by inhibiting endoplasmic reticulum stress via Piezo1 channels - Song, Xuyu; Liu, Ying; Shen, Xianhui; Zhang, Lei; Kong, Hongwei; Chen, Siyi; Sheng, Lisong; Sun, Rong (Frontiers in Pharmacology, 2025)
BackgroundShengyu decoction (SYD) is a classic and excellent prescription of traditional Chinese medicine (TCM). The innovative use of SYD by Chinese medical master Prof. Qi Shi in the treatment of knee osteoarthritis (KOA) has achieved considerable clinical outcomes. However, the current weakness is the lack of studies on the active ingredients and mechanisms of SYD.PurposeTo evaluate the role of SYD in reducing KOA cartilage damage as well as to explore the active ingredients and mechanisms of SYD.MethodsThe KOA rat model and chondrocyte model were established. This study employed various molecular biology techniques to clarify the role of SYD in vivo and in vitro. The active ingredients and mechanisms of SYD were analyzed through ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS), RNA sequencing, molecular docking, and surface plasmon resonance (SPR). Finally, rescue experiments were conducted to verify the mechanisms.ResultsThe results revealed that SYD could significantly reduce cartilage tissue lesions, inhibit inflammation, and regulate proliferation–apoptosis balance. Transcriptome analysis showed an increase in the expressions of Piezo1, Xbp1, and Atf6 in KOA, and SYD downregulated them. UPLC-Q-TOF-MS analysis revealed four bioactive compounds of SYD, which were further confirmed to directly interact with Piezo1 through molecular docking and SPR assays. Furthermore, SYD downregulated the calcium ion concentration and the intensity of Piezo1 and ERS. Meanwhile, in the rescue experiment, Yoda1, the agonist of Piezo1, antagonized the pharmacological effects of SYD.ConclusionThe present results provide strong evidence that SYD protected articular cartilage via inhibiting the Piezo1-mediated ERS signaling pathway. Overall, our work emphasizes the pivotal role of TCM in addressing medical challenges and provides new ideas for the treatment of KOA.